THE IMPACT OF CAPITAL STRUCTURE AND FIRM SIZE ON FINANCIAL PERFORMANCE - Tanggor Sihombing; Zessica Zhou (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2019)
This research aims to prove empirically the impact of financial factors related to finacial performance which consist of capital structure and firm size to financial performance using return on asset, return on equity, and current ratio as measurements. The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017, as the observation was conducted in said time period. Purposive sampling used with a total sample of 32 companies with 5 years observation period for each company. Total asset, total liability, total equity, current asset, current liability, net income were taken from the companies’ annual report, assessed regarding to some criteria in the regulation and best practice. Data Analysis method used is multiple linear regression analysis. The results showed that capital structure and firm size simulatneously significant in affecting financial performance using return on asset, return on equity, and current ratio as measurements.